Prognostic Markers in Term Infants with Hypoxic–Ischemic Encephalopathy: Comparative Analysis of MRI, EEG, and Apgar Scores - Goenka, Ajay; Yozawitz, Elissa (Journal of Pediatric Neurology, 2018)
Hypoxic–ischemic encephalopathy (HIE) is a frequent cause of perinatally acquired brain injury resulting in abnormal neurological consequences. In this retrospective study, we evaluated 68 neonates with clinical evidence of HIE to investigate the utility of magnetic resonance imaging (MRI), electroencephalography (EEG), and Apgar scores, individually and in combination, as predictors of long-term outcome. Six infants died during treatment, and 46 of the remaining 62 infants (74%) received follow-up neurological assessments at ages 6 to 24 months. The outcome was dichotomously classified as good (reflecting “normal development”) or as poor (reflecting “neurological deficits” based upon attainment of developmental milestones or death). Abnormal Apgar scores, MRIs, and EEGs had sensitivities of 50, 84, and 95% for predicting “neurological deficit.” Corresponding specificities were 85, 66, and 18%. However, the combination of abnormal Apgar scores, MRIs, and EEGs in predicting poor outcomes (i.e., “neurological deficits” or death) had sensitivity and specificity of 100%. In addition, the combination of abnormal Apgar scores, MRIs, and EEGs provided a positive predictive value of 100% in assessing poor outcome as compared with 73% (p = 0.2) for Apgar scores, 71% (p = 0.01) for MRIs, and 56% (p = 0.001) for EEGs.
Keywords: hypoxic–ischemic encephalopathy; magnetic resonance imaging; electroencephalography; Apgar scores